AMBIDEKSTERITAS ORGANISASIONAL: ISU RISET DAN ANTESEDEN - Noekent, Vitradesie (Universitas Muhammadiyah Surakarta, 2016)
There are two main issues in organizational ambidexterity.Â Firstly, structure-based organizational ambidexterity argued that the tension between exploration and exploitation can reconcile by creating the separated organizational structure for different activity.Â Secondly, contextual-based organizational ambidexterity stressed the influence of organizational context to create behavior for balancing exploration and exploitation activities.Â This article argue that he structural dimension and organizational behavior will produce micro foundation which is the interaction between both dimension will produce exploration and exploitation processes as organizational outcome.